anonymous
  • anonymous
7+3d-5=-1+2d-12+d solve
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
collect like terms and simplify..
anonymous
  • anonymous
having trouble with it
anonymous
  • anonymous
solve for d do you konw how

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
tried solving but I don't think I did it right
anonymous
  • anonymous
can you show us??
anonymous
  • anonymous
yeah
anonymous
  • anonymous
2+3d=-13+3d +2 +2 3d=-11+3d d=this is where I get lost
anonymous
  • anonymous
2 + 3d = -13 + 3d subtract 3d from both sides 2 + 3d - 3d = -13 + 3d - 3d combine like terms 2 = -13 (incorrect) There is no solution to this problem
anonymous
  • anonymous
Solution for 7+3d-5=-1+2d-12+d equation: Simplifying 7 + 3d + -5 = -1 + 2d + -12 + d Reorder the terms: 7 + -5 + 3d = -1 + 2d + -12 + d Combine like terms: 7 + -5 = 2 2 + 3d = -1 + 2d + -12 + d Reorder the terms: 2 + 3d = -1 + -12 + 2d + d Combine like terms: -1 + -12 = -13 2 + 3d = -13 + 2d + d Combine like terms: 2d + d = 3d 2 + 3d = -13 + 3d Add '-3d' to each side of the equation. 2 + 3d + -3d = -13 + 3d + -3d Combine like terms: 3d + -3d = 0 2 + 0 = -13 + 3d + -3d 2 = -13 + 3d + -3d Combine like terms: 3d + -3d = 0 2 = -13 + 0 2 = -13 This equation is invalid, the left and right sides are not equal, therefore there is no solution
anonymous
  • anonymous
boom
anonymous
  • anonymous
nicely done jaylan :)
anonymous
  • anonymous
thanks
anonymous
  • anonymous
make sure you close the question when your done

Looking for something else?

Not the answer you are looking for? Search for more explanations.